2022
DOI: 10.1007/s11274-022-03359-5
|View full text |Cite
|
Sign up to set email alerts
|

Constitutive chitosanase from Bacillus thuringiensis B-387 and its potential for preparation of antimicrobial chitooligomers

Abstract: RAS: U mskij institut biologii RAN Nailya Galimzianova Ufa Scienti c Center of the Russian Academy of Sciences: FGBNU U mskij federal'nyj issledovatel'skij centr Rossijskoj akademii nauk

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 55 publications
0
4
0
Order By: Relevance
“…Meanwhile, the pH stability was determined by incubating the enzyme solutions with the pH buffers, including acetate-sodium buffer (pH 3.0–6.0), phosphate buffer (pH 6.0–8.0), Tris-HCl buffer (pH 8.0–9.0), and glycine–NaOH buffer (pH 9.0–10.0) at 37 °C for 1 h. And the optimal temperature of the enzyme was measured under reaction temperatures ranging from 30–70 °C. The thermal stability was determined by incubating the purified OUC-CsnPa at 30–70 °C for 1 h . The highest enzyme activity was defined as 100%.…”
Section: Methodsmentioning
confidence: 99%
“…Meanwhile, the pH stability was determined by incubating the enzyme solutions with the pH buffers, including acetate-sodium buffer (pH 3.0–6.0), phosphate buffer (pH 6.0–8.0), Tris-HCl buffer (pH 8.0–9.0), and glycine–NaOH buffer (pH 9.0–10.0) at 37 °C for 1 h. And the optimal temperature of the enzyme was measured under reaction temperatures ranging from 30–70 °C. The thermal stability was determined by incubating the purified OUC-CsnPa at 30–70 °C for 1 h . The highest enzyme activity was defined as 100%.…”
Section: Methodsmentioning
confidence: 99%
“…It is likely that the positive charges of COSs interact with negative charges on the bacterial cell surfaces, leading to inhibition of cell growth. In contrast, the shorter COSs (DA = 0.15; DP = 2, 3, and 4) and low molecular weight chitosan produced by a chitosanase from Bacillus thuringiensis B-387 from chitosan polysaccharide (DA, 0.15), of which the average MWs were in a range of 14–46 kDa, exhibited greater antibacterial activities toward E. coli in vitro (MIC, 70 mg·mL −1 ) in comparison with the initial polysaccharides (MIC, 120 mg·mL −1 ) [ 22 ]. Ganan et al analyzed the antifungal activities of soluble and well-defined COSs.…”
Section: Biological Activities Of Cossmentioning
confidence: 99%
“…In contrast, the shorter COSs (DA = 0. 2, 3, and 4) and low molecular weight chitosan produced by a chitosanase from thuringiensis B-387 from chitosan polysaccharide (DA, 0.15), of which the avera were in a range of 14-46 kDa, exhibited greater antibacterial activities toward vitro (MIC, 70 mg•mL −1 ) in comparison with the initial polysaccharides (M mg•mL −1 ) [22]. Ganan…”
Section: Antimicrobial Activitymentioning
confidence: 99%
“…It was shown that oligosaccharides of chitin and chitosan produced with the participation of extracellular chitinases and chitosanases of Bt subsp. dendrolimus B-387 possess high bactericidal and fungicidal activity [122]. Similarly, endophytic B. cereus XB177R, which show high chitinase activity effectively protected eggplant plants from bacterial wilt caused by R. solanacearum [69].…”
Section: Production Of Fungicidal and Bactericidal Compounds And Trig...mentioning
confidence: 99%